Adventures in Marxism. - Berman, Marshall (London Verso, 2000)
A new beginning for Marxism might just be on the horizon of a landscape despoiled by Soviet communism and a now wobbling world capitalism. The attention attracted by the 150th anniversary of The Communist Manifesto included laudatory references to Marx in venues as unexpected as The New York Times and The New Yorker. More predictably, the tributes in such publications focused on the strength of Marx as a critic of capital or a powerful wordsmith, rather than as an advocate of communism. But, if Marxism is to enjoy a rebirth in the coming century, appreciation needs to move beyond its value as a critical tool or a literary pleasure. The emancipatory potential of Marxism, its capacity to configure a world beyond the daily grind of selling one?s labor to stay alive, will have to be established anew. No one has made a better start to this task than the esteemed critic and writer Marshall Berman. Berman first read The Communist Manifesto in the same week as Arthur Miller?s Death of a Salesman while at high school. A few years later, now a student at Columbia University, he was handing out copies of Marx?s 1844 Manuscripts, purchased for 50 cents each at the (Soviet) Four Continents Bookstore in New York, as holiday presents for friends and relatives. Here was the beginning of a lifelong engagement with Marxism that, as this volume demonstrates, has been both consistent and refreshing. In these pages are discussions of work on Marx and Marxism by Edmund Wilson, Jerrold Siegel, James Billington, Georg Lukcs, Irving Howe and Isaac Babel. They are brought together in a single embrace by Berman?s spirited appreciation of Marxism as expressive, playful, sometimes even a little vulgar, but always an adventure.
Includes index
Keywords: Marxism